Pola Komunikasi Dakwah Pada Majelis Taklim: (Studi Kasus Pada Majlis Ta’lim Al-Mawaddah Bani Hasan Kp. Sinangmangu Mancak Serang) - Kholid Kholid (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah UIN Sultan Maulana Hasanuddin Banten, 2022)
Delivering da'wah messages must be done with various good and correct communication patterns. So that the da'wah material delivered can be understood and carried out by the congregation. This research discusses in more detail about the communication patterns of da'wah at the Majlis Ta'lim Al-Mawaddah Bani Hasan Mancak Serang. The purpose of this study was to find out how the pattern of da'wah communication in Majlis ta'lim Al-Maaddah. What da'wah communication patterns are used at the ta'lim al-Mawaddah majlis, what routine activities are carried out in maintaining congregational solidarity